PENGUATAN BUDAYA LITERASI UNTUK PENINGKATAN MUTU BELAJAR SISWA SMPN KOTA BANDUNG - susilawati, lina (Wali Pikir: Journal Of Education, 2023)
The problem that arises in this study is the low reading motivation for students in junior high school and the availability of non-learning books in schools is inadequate. The purpose of writing specifically is to examine the objectives and development programs of literacy culture, to know the implementation of the literacy culture program in learning in science and social studies subjects, to know the problems faced by teachers in implementing a culture of literacy, to know solutions and efforts to improve the literacy culture to improve student learning quality. The method used is descriptive method with a qualitative approach. The form of implementation of literacy activities is carried out in the form of reading 15 minutes, making journals, making book reviews, and redathon once a month. The implementation of strengthening literacy culture activities has been integrated into science and social studies subjects. Factors that hinder the strengthening of literacy culture in general students do not yet understand the importance of literacy, besides that tool and facilities are inadequate. The conclusion of the results of this study is that literacy activities have not been carried out optimally, this can be seen from the low percentage of student visits to the library.